Neuropsychology's Role in Pediatric Epilepsy Surgery - Shurtleff, Hillary (Journal of Pediatric Epilepsy, 2017)
Neuropsychology plays an essential role in pediatric epilepsy surgery. Evaluations provide information to inform presurgical decision-making by addressing localization and lateralization of deficits and by informing risk of postsurgical decline. The pediatric neuropsychologist also assists with multiple additional procedures, including the Wada or Intracarotid amobarbital procedure, functional magnetic resonance imaging, and brain mapping (on the ward and in the operating room), to measure localization and lateralization of eloquent cortex as well as adequacy of brain tissue to be resected and risk of resection of specific cortex. Neuropsychology provides postsurgical outcome information not only for individual patients, but as “quality control” for epilepsy surgery. Multiple factors complicate individual patient data interpretation, and these factors are essential to understand and consider. Developmental considerations are paramount. Although methodological differences between studies can also make surgical outcome studies challenging to interpret, neuropsychological data suggest that pediatric surgery can improve developmental outcomes and trajectories, particularly if resection is done early and without lengthy presurgical seizure duration, although longer seizure duration and polypharmacy, more widespread disease, and larger areas of resection, particularly of critical eloquent cortex, can be costly to the individual patient. Additional and more refined research is needed.
Keywords: neuropsychology; epilepsy surgery; pediatric psychology; fMRI; Wada